Implementation of additional educational programs for schoolchildren in swimming training - Prokhorenko A.A.; Antonov A.V.; Kolesnikov N.V.; Striga S.I. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to experimentally substantiate the optimal set of special sports swimming exercises for teaching schoolchildren to swim as part of an additional general education program. Methods and structure of the study. The following research methods were used to solve the problems such as: theoretical analysis and summarization of literary sources, interviews, pedagogical observation, and pedagogical experiments. Results and conclusions. Effective exercises and their sequence of application in swimming instruction have been identified. The proposed set of exercises allows improving physical fitness and strengthening the health of schoolchildren studying under an additional general education program. During classes, the time required to master basic swimming skills is significantly reduced, and correct swimming technique is established, which allows students to move on to more complex skills in a short period of time.